The importance of sexuality in the health of the elderly (Research, Society and Development, 2023)
Population aging is intensified by the reduction in the number of births and the drop in mortality, despite this, this phase is surrounded by prejudice, which influences the sociocultural construction of myths and taboos about sexuality in old age. This study has as main objective to identify in the scientific literature the importance of sexuality in the health of the elderly. This is an integrative literature review study, with searches for articles in the databases available in the VHL (Virtual Health Library), such as LILACS (Latin American Literature in Health Sciences), MEDLINE (Medical Literature Analysis and Retrieval Sistem online) and BDENF (Nursing Database), from June to September 2022. Eight articles were selected in the databases, according to the inclusion and exclusion criteria, showing that most of the elderly researched in the studies declared the importance of sexuality in old age, as well as the influence of the practice on quality of life. It is concluded that the elderly understand sexuality and its active practice, as well as its numerous benefits, in addition to being fully aware of their needs and desires, however, they are still afraid of the prejudice and stigma that unfortunately still exists in around old age. It was also confirmed the existence of several factors that hinder the satisfactory sexual practice of the elderly and the low knowledge about Sexually Transmitted Infections and low adherence to the use of condoms.